Pentingnya Media Pembelajaran dalam Proses Belajar Mengajar - Amelia Putri Wulandari; Annisa Anastasia Salsabila; Karina Cahyani; Tsani Shofiah Nurazizah; Zakiah Ulfiah (Journal on Education, 2023)
Learning media is one component in the learning process. Learning media is a tool that can help teachers convey learning material so that children can have an interest and interest in the learning material presented. It's just that in using learning media, teachers must be able to choose learning media that are appropriate to the material to be delivered and teachers must also adjust to the character of their students in choosing learning media. Some teachers still do not understand how important it is to use appropriate learning media so that learning does not feel monotonous and boring for students. Therefore, in this study the authors used the method of library research (library research) to examine how important appropriate instructional media is for the teaching and learning process in elementary schools. The results of the study state that appropriate learning media is very important in supporting student learning. Selection of appropriate learning can help students to understand the learning material delivered by the teacher. Learning media can provide concrete experience and as an intermediary that helps student learning.